Independent predictors and risk score for intraprocedural rupture during endovascular treatment of small ruptured intracranial aneurysms (<5 mm) - Peng, Fei; Feng, Xin; He, Xiaoxin; Niu, Hao; Zhang, Hong; Tong, Xin; Zhang, Baorui; Xia, Jiaxiang; Chen, Xuge; Xu, Boya; Qi, Peng; Lu, Jun; et al. (Frontiers in Neurology, 2022)
Background and Purpose Intraprocedural rupture (IPR) is a devastating complication of endovascular treatment (EVT). Small-sized and ruptured aneurysms are independent predictors of IPR, which presents a technical challenge during EVT. We aimed to develop a score to quantify the individual patient risk of IPR in EVT of small (<5mm) ruptured aneurysms (SRAs). Methods A retrospective review was performed to interrogate prospectively maintained databases at two academic institutions in China from January 2009 to October 2016. We collected intraoperative angiograms and medical records to identify independent predictors of IPR by using univariate and multivariable analyses. A risk score for IPR was derived from the multivariable logistic regression analyses. Results Of the 290 patients enrolled, IPR occurred in 16 patients (5.5%). Univariate analysis showed that the rate of IPR was significantly higher in patients having aneurysms with a small basal outpouching (SBO), in patients having aneurysms concomitant with adjacent moderate atherosclerotic stenosis (ACAMAS), and in former or current smokers. Multivariate analyses showed that SBO (OR: 3.573; 95% CI: 1.078-11.840; P=0.037), vascular eloquence (VE; OR: 3.780; 95% CI: 1.080-13.224; P=0.037) and ACAMAS (OR: 6.086; 95% CI: 1.768-20.955; P=0.004) were significantly and independently associated with IPR. A three-point risk score (S-V-A) was derived to predict IPR (SBO [yes=1], VE [yes=1], and ACAMAS [yes=1]).